2016
DOI: 10.1123/jab.2015-0136
|View full text |Cite
|
Sign up to set email alerts
|

Loaded Vertical Jumping: Force–Velocity Relationship, Work, and Power

Abstract: The aims of the current study were to explore the pattern of the force-velocity (F-V) relationship of leg muscles, evaluate the reliability and concurrent validity of the obtained parameters, and explore the load associated changes in the muscle work and power output. Subjects performed maximum vertical countermovement jumps with a vest ranging 0-40% of their body mass. The ground reaction force and leg joint kinematics and kinetics were recorded. The data revealed a strong and approximately linear F-V relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 0 publications
8
36
1
Order By: Relevance
“…Such results have been consistently observed from cycling [1316], jumping [1719], running [20, 21], leg push offs [4, 2224], lifting [13, 25, 26] etc. Of utmost importance is that most of the cited studies revealed the correlation coefficients of the linear model applied to individual sets of data well above 0.9.…”
Section: Force-velocity Relationship Of Muscles Performing Functiosupporting
confidence: 54%
See 2 more Smart Citations
“…Such results have been consistently observed from cycling [1316], jumping [1719], running [20, 21], leg push offs [4, 2224], lifting [13, 25, 26] etc. Of utmost importance is that most of the cited studies revealed the correlation coefficients of the linear model applied to individual sets of data well above 0.9.…”
Section: Force-velocity Relationship Of Muscles Performing Functiosupporting
confidence: 54%
“…Of utmost importance is that most of the cited studies revealed the correlation coefficients of the linear model applied to individual sets of data well above 0.9. In addition, no significant differences in the strength of the relationships were found between the linear and polynomial regression models applied on the same sets of F and V data [18, 19, 25] suggesting that the assessed F-V relationships could be considered linear for further computation. Of importance could also be that the parameters depicting the maximum F, V and P of the tested muscles (i.e., the regression parameters F 0 , V 0 , and P 0 , respectively) proved to be highly reliable [17, 18, 2426] and at least moderately valid [15, 1719].…”
Section: Force-velocity Relationship Of Muscles Performing Functiomentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together with typical variability of Hcmd of approximately 3-10 cm observed from consecutive jumps of the same subjects (Mandic et al, 2015; Markovic et al, 2014), such differences proved to result in prominent changes in the directly measured force and power output. Therefore, the present study adds to the evidence that the variations in Hcmd decouple jumping performance from the muscle force and power output (Bobbert et al, 2008; Feeney et al, 2016; Mandic et al, 2015; Markovic et al, 2014). Specifically, it shows that the selected control strategy based on a relatively short preferred Hcmd provides considerably higher force and power output than observed in the same jumps conducted from the optimum Hcmd that maximize Hjump.…”
Section: Discussionmentioning
confidence: 62%
“…The parameters obtained from the linear F-V relationship have consistently revealed high reliability (Jaric, 2015). In addition, the abilities to generate high movement velocity or resistance to high external load have been shown to be determined by V 0 (Feeney, Stanhope, Kaminski, Machi, & Jaric, 2016) and F 0 (Driss, Vandewalle, Le Chevalier, & Monod, 2002), respectively, while ballistic performance is largely dependent not only on P M (Samozino, Rejc, Di Prampero, Belli, & Morin, 2012;Vandewalle, Peres, Heller, Panel, & Monod, 1987) but also on an optimum balance between F 0 and V 0 (i.e., F-V slope) (Jiménez-Reyes, Samozino, Brughelli, & Morin, 2017;Samozino et al, 2014).…”
Section: Introductionmentioning
confidence: 99%